A framework for developing Real-Time OLAP algorithm using multi-core processing and GPU: Heterogeneous computing - Alzeini, Haytham I M; Hameed, Shihab A.; Habaebi, Mohamed Hadi (2013)
The overwhelmingly increasing amount of stored data has spurred researchers seeking different methods in order to optimally take advantage of it which mostly have faced a response time problem as a result of this enormous size of data. Most of solutions have suggested materialization as a favourite solution. However, such a solution cannot attain Real-Time answers anyhow. In this paper we propose a framework illustrating the barriers and suggested solutions in the way of achieving Real-Time OLAP answers that are significantly used in decision support systems and data warehouses.